Shape memory polyurethane with polydopamine-coated nanosheets: Simultaneous enhancement of recovery stress and strain recovery ratio and the underlying mechanisms - Phua, Si Lei (2016)
Two different sizes of polydopamine-coated layered double hydroxides (D-LDHs) are incorporated into polycaprolactone-based polyurethane (PU) to enhance the mechanical and shape memory properties of the PU. The results show that D-LDH interacts strongly with hard segments and hence enhancing phase separation between hard and soft segments. It is found that the tensile moduli of the PU/D-LDH nanocomposites are much higher than that of neat PU at 60 oC. In comparison with neat PU, the nanocomposite with 2 wt% of small D-LDH exhibits a 60% increase in recovery stress while shape fixity and strain recovery ratio are also improved simultaneously. This is because at low filler loading, most small D-LDH nanosheets interact with hard domains and they are not large enough to connect neighbor hard domains. They can hence reinforce the hard domains without sacrificing the elasticity of the system. Two-dimensional X-ray diffraction studies indicate that most small D-LDH nanosheets are able to rotate back from aligned state to original random state in shape recovery process, justifying the improved strain recovery ratio.